THE EFFECT OF FIRM SIZE IN MODERATING MACRO-MICRO ECONOMIC POLICIES’ IMPACT ON CASH HOLDING - Faisal Bimantara; Abid Dzajuli; Vita, Ervita Safitri; Wani Fitriah (Yayasan Nuraini Ibrahim Mandiri, 2025)
This study aims to determine the influence of Capital Expenditure, Capital Structure: DER, Net Working Capital, Cash Flow, and Inflation on Cash Holding in Financial Sector companies listed on the Indonesia Stock Exchange 2019-2023 and is Firm Size as a moderation variable able to moderate the relationship of each variable to Cash Holding? This study is associative with seven variables: Capital Expenditure, DER, Net Working Capital, Cash Flow, Inflation, Cash Holding, and Firm Size. The sample consists of 38 financial sector companies listed on the IDX in 2019–2023. Data analysis uses Moderated Regression Analysis (MRA). The results show that Capital Expenditure and Net Working Capital have a significant negative effect on Cash Holding, while DER and Cash Flow have a significant positive effect. Inflation does not have a significant effect directly, but it has a significant effect if moderated by Firm Size. Firm Size also moderates significantly the influence of Capital Expenditure, DER, Net Working Capital, and Cash Flow on Cash Holding.